Operative management and outcomes of brachial artery revascularization following delayed presentation of traumatic brachial artery injury: surgical persistence rewarded - Kumar, Madhur; Pramanik, Subrata; Gupta, Anubhav (International Surgery Journal, 2021)
Background: Dearth of expertise to manage vascular trauma spiraled with delay in diagnosis and referral to tertiary care centers continue to plague a developing nation like India. The brachial artery is the commonest artery to be injured in extremity following trauma. Although the patients present late, revascularization to salvage the limb and to maintain its function is advocated. This retrospective study was done to evaluate the management and outcomes of brachial artery revascularization in patients with delayed presentation of traumatic brachial artery injury. Methods: Twenty-six patients of traumatic brachial artery injury who met the inclusion criteria during 1-year study period (August 2019 to July 2020) were included. Patients with iatrogenic vascular injury, severe vascular injury associated with massive orthopaedic neuromuscular injury (i.e., crush injury), mottled upper limb and injury to neck, chest, abdomen, lower limbs or any pseudoaneurysm were excluded. Data were analysed. Results: Amongst 26 patients studied, 24 (92.30%) patients had complete transection of the artery. Of these, 19 (79.16%) had primary repair in the form of end-to-end anastomosis and 7 (29.16%) underwent reverse interposition saphenous vein grafting. Two patients with partial laceration of brachial artery underwent primary (lateral) repair. Associated fracture of humerus was managed with internal fixation following revascularization. Four cases underwent end to end repair of median nerve. Majority, 22 (84.61%) had good functional outcome and 4 (15.38%) had satisfactory functional results. Limb salvage rates was 100%. Conclusions: Revascularization beyond warm ischemia time is still desirable to prevent limb loss. Traumatic neurological injury affects the functional outcome.